1999
DOI: 10.1111/j.1469-8749.1999.tb00605.x
|View full text |Cite
|
Sign up to set email alerts
|

Executive function of children with extremely low birthweight: a case control study

Abstract: This study examines the executive function (EF) skills of extremely‐low‐birthweight (ELBW) children at school compared with their peers. Thirty children with ELBW and 50 control children (both with a mean age of 62 ±4 months) were administered tests of EF including the Tower of Hanoi task, Finger Sequencing task, and Tapping Test. Children with ELBW, including those who scored more than 1 SD below the mean on the Peabody Picture Vocabulary Test – Revised, scored significantly lower than their peers on all exec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…Repeated over time, this process could help to explain the social position of a child in the peer group: social isolation, lack of mutual friends, and victimization. Recent studies indicate that children born preterm without major motor, intellectual or sensory disabilities show a higher incidence of subtle deficits in executive function, perception, memory and attention at school age (Luoma et al 1998, Harvey et al 1999, Luciana et al 1999, Isaacs et al 2000, Aylward 2002). The effect of these cognitive function deficits on the way in which the child encodes, interprets, and responds in a social situation has not been documented in the field of prematurity.…”
Section: Discussionmentioning
confidence: 99%
“…Repeated over time, this process could help to explain the social position of a child in the peer group: social isolation, lack of mutual friends, and victimization. Recent studies indicate that children born preterm without major motor, intellectual or sensory disabilities show a higher incidence of subtle deficits in executive function, perception, memory and attention at school age (Luoma et al 1998, Harvey et al 1999, Luciana et al 1999, Isaacs et al 2000, Aylward 2002). The effect of these cognitive function deficits on the way in which the child encodes, interprets, and responds in a social situation has not been documented in the field of prematurity.…”
Section: Discussionmentioning
confidence: 99%
“…17 In reality, despite apparently exhibiting intellectual function within normal limits when submitted to standardized tests, children born prematurely are at increased risk of academic performance disabilities. [18][19][20][21][22][23][24][25][26][27][28][29][30] This risk appears to increase in line with reductions in birth weight. 16,19 The academic difficulties exhibited by extremely low birth weight children reflect their vulnerabilities in terms of visuospatial, visuomotor and verbal abilities.…”
Section: Introductionmentioning
confidence: 92%
“…[27][28][29][30][31][32][33][34][35][36][37][38][39] Randomeffects meta-analysis revealed that preterm-born children had significantly lower receptive vocabulary scores compared with term-born children, as indicated by the combined effect size of d = -0.45 (95% CI: -0.59 to -0.30; P , .001) (Fig 2). Significantly lower receptive vocabulary scores in preterm-born children compared with term-born children were found in 8 of the 13 studies.…”
Section: Simple Language Functionmentioning
confidence: 99%
“…Significantly lower receptive vocabulary scores in preterm-born children compared with term-born children were found in 8 of the 13 studies. [28][29][30][31][32][33][34]39 No statistically significant heterogeneity between the studies was found (Q = 19.35, P = .08; I 2 = 38.0). A funnel plot and Egger test (P = .92) showed no underlying publication bias.…”
Section: Simple Language Functionmentioning
confidence: 99%